Design of MPC for Superheated Steam Temperature Control in a Coal-fired Thermal Power Plant - A. Yasmine Begum; G. V. Marutheeswar (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
A superheater is a vital part of the steam generation process in the boiler-turbine system. Reliable control of temperature in the superheated steam temperature system is essential to guarantee efficiency and high load-following capability in the operation of coal-fired Thermal power plant. The PI and PID controllers are extensively used in cascade control of secondary superheated steam temperature process.The design and implementation of a Model Predictive Control (MPC) strategy for the superheated steam temperature regulation in a thermal power plant is presented. A FOPTD model  is derived from  the dynamic model of the superheater. This model is required by the MPC algorithm to calculate the future control inputs. A new MPC controller is designed and its performance is tested through simulation studies. Compared with the superheater steam temperature control using a conventional PID controller, the steam temperature controlled by the MPC controller is found to be more stable. The stable steam temperature leads to energy saving and efficient plant operation, as verified by the simulation results.